Psychological generators of stress-headaches. - Berry, Juanita Kay Miller; Drummond, Peter D. (Journal of Behavioral Medicine, 2018)
Psychological stress triggers headaches, but how this happens is unclear. To explore this, 38 migraine sufferers, 28 with tension-type headache (T-TH) and 20 controls rated nausea, negative affect, task-expectancies and headache at 5-min intervals during an aversive 20-min mental arithmetic task with a fixed failure rate. Blood pressure and pulse rate were measured every 3 min and salivary cortisol was sampled before and after the task. Multiple regression analysis indicated that irritation, anxiety and the absence of sluggishness (i.e., alertness) independently predicted increases in headache intensity during the task ( p < .001), but increases in headache were unrelated to changes in cardiovascular activity or cortisol. Changes that preceded headache onset were explored in repeated measures ANOVAs, comparing those who developed headache with those who did not. In general, nausea, negative affect and self-efficacy expectancies were higher in participants who went on to develop headache than in those who remained headache-free ( p < .05 to p < .001). Together, these findings suggest that headache developed when participants overextended themselves during a stressful task, adopting an information processing style which impeded emotional adjustment to changing situational demands. Learning to modify perceptions of threat, and adopting a more flexible, less outcome-dependent processing style, might help to prevent headache from spiralling upward.